Stochastic Queuing System Model Design Based on Stakeholder Aspirations - Widodo, Imam Djati; Parkhan, Ali; Qurtubi, Qurtubi (Journal of Applied Data Sciences, 2024)
A good queuing system will provide satisfaction and trust for consumers and operational cost efficiency for service providers. This study aims to obtain the optimal number of service facilities by considering the aspirations of stakeholders, namely customers and service providers. Using aspiration theory, this research contributes to obtaining a dynamic solution to the number of service facilities with reference to service operating costs that can be determined with certainty and waiting costs that vary based on customer profiles. The study began by designing sampling for arrival time and service time data based on simple random sampling. The probability distributions of arrival time and service time are determined based on the data collection results of the sampling design. Based on the queuing profile and distribution of the two data, a suitable queuing model is built. Poisson distribution-based multi-channel queue model is constructed ((M/M/c):(GD/∞/∞)), and an optimization analysis is carried out on the number of service facilities provided by considering the aspirations of the two stakeholders. The results showed that based on stakeholder aspirations, optimal conditions were achieved at the number of servers c = 2 if the waiting cost (C2): IDR 0/hour≤ C2 ≤ IDR 11,076/hour, and the number of servers c = 3 if the waiting cost (C2): IDR 11,076/hour ≤ C2 ≤ IDR 120,690/hour.  Given that there are two conditional alternatives, the company can decide subjectively to take preventive and adaptive actions proactively according to the customer's appreciation of the waiting time in the company. Flexibility in opening service facilities will require the availability of workers and facilities to be provided. Multi-skilled workers will significantly help the flexibility of the system being built. Future research certainly needs to conduct a more in-depth study related to monthly fluctuations in arrival and service times within that period.